Estimasi Minimaks Operator Linear dalam Ruang Hilbert= A Minimax Estimation of a Linear Operator in a Hilbert Space - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT A minimax criterion has been used to estimate a linear operator in a Hilbert space. The existence and uniqueness of an estimator is proven in a general context. In spite of its universality, the practical characteristics of an optimal solution does not appear feasible as shown by a particular example. The result of a minimax estimator is shown to be connected with a smoothing spline.